COMPARATIVE EVALUATION AND STUDING OF SOME INDIGENOUS AND INTRODUCED RED GRAPE VARIETIES - H. Fataliyev; Y. Lazgiyev; M. İmamguliyeva; E. Haydarov; Sh. Fataliyeva; Sh. Huseynova; S. Agayeva; S. İsganderova; A. Askarova; İ. Askarova (Harčova Nauka ì Tehnologìâ, 2023)
Azerbaijan is one of the ancient wine-growing country, and it is famous by its rich assortment of local grapes. Historically, in our country well-known brand wines have been prepared from aboriginal red grape varieties. Among them, we can mention branded Kurdamir kagoru, Shamakhi kagoru, Madasa and Khindogni natural wines, etc. wines made from such autochthonous grape varieties won the favor of consumers with their unique physical-chemical and organoleptic characteristics. In line with it, in recent years, to the country introduced a number of valuable grape varieties such as Merlot, Cabernet Sauvignon, Syrah and others. It is actually relevant comparative evaluation of such varieties cultivated in local conditions, including red ones.